An externally constrained hybrid regime: Hungary in the European Union. Issue 7 (3rd October 2018) - Bozóki, András; Hegedűs, Dániel
ABSTRACT: The paper focuses on the unique, role model characteristics of the Hungarian hybrid regime, the Hungarian political system's new incarnation forged in the past years' democratic backsliding process. Following the short review of the main hybrid regime literature and the key analyses putting the democratic quality of the Hungarian political system under the microscope, the paper argues that Hungary's European Union (EU) membership, the competencies of EU institutions, and the scope of EU law have played a crucial role in the development of the system's unique characteristics. Based on this argument, the paper qualifies Hungary as an "externally constrained hybrid regime". However, the EU does not only fulfil system constraining functions regarding the Hungarian regime, but performs system support and system legitimation functions as well. Ultimately, the changing scope of these functions, determined by the European integration's internal dynamics, influences first and foremost the Hungarian power elite's strategic considerations about the country's future EU membership.